Readmission following surgical stabilization of rib fractures: Analysis of incidence, cost, and risk factors using the Nationwide Readmissions Database. Issue 2 (20th August 2021) - Aalberg, Jeffrey J.; Johnson, Benjamin P.; Hojman, Horacio M.; Rattan, Rishi; Arabian, Sandra; Mahoney, Eric J.; Bugaev, Nikolay
Abstract : Supplemental digital content is available in the text. Abstract : BACKGROUND: Surgical stabilization of rib fractures (SSRF) has become increasingly common for the treatment of traumatic rib fractures; however, little is known about related postoperative readmissions. The aims of this study were to determine the rate and cost of readmissions and to identify patient, hospital, and injury characteristics that are associated with risk of readmission in patients who underwent SSRF. The null hypotheses were that readmissions following rib fixation were rare and unrelated to the SSRF complications. METHODS: This is a retrospective analysis of the 2015 to 2017 Nationwide Readmission Database. Adult patients with rib fractures treated by SSRF were included. Univariate and multivariate analyses were used to compare patients readmitted within 30 days with those who were not, based on demographics, comorbidities, and hospital characteristics. Financial information examined included average visit costs and national extrapolations. RESULTS: A total of 2, 522 patients who underwent SSRF were included, of whom 276 (10.9%) were readmitted within 30 days. In 36.2% of patients, the reasons for readmissions were related to complications of rib fractures or SSRF. The rest of the patients (63.8%) were readmitted because of mostly nontrauma reasons (32.2%) and new traumatic injuries (21.1%) among other reasons. Multivariate analysis demonstrated that ventilator use, discharge other than home, hospital size, and medical comorbidities were significantly associated with risk of readmission. Nationally, an estimated 2, 498 patients undergo SSRF each year, with costs of US 176 million for initial admissions and US 5.9 million for readmissions. CONCLUSION: Readmissions after SSRF are rare and mostly attributed to the reasons not directly related to sequelae of rib fractures or SSRF complications. Interventions aimed at optimizing patients' preexisting medical conditions before discharge should be further investigated as a potential way to decrease rates of readmission after SSRF. LEVEL OF EVIDENCE: Epidemiological study, level III.